Synthesis of Methyl Cellulose from Rice Husk Cellulose (Oryza sativa L.) with Methylene Chloride Through Etherification Reaction - Adil Ginting; Novi Yosefin Sinabariba (Talenta Publisher, 2023)
Methyl cellulose is synthesized by an etherification reaction between Î±-cellulose created by isolating rice husks (Oryza sativa L.) with methylene chloride. Methylcellulose synthesis is performed by combining 1 g Î±-cellulose with acetone solvents at variations of methylene chloride 6 g, 8 g, 10 g, 12 g, and 14 g for 6 hours, resulting in 0.47 g, 0.60 g, 0.58 g; 0.51 g; and 0.69 g of methylcellulose. The results of methyl cellulose synthesis were tested with Degrees of Substitution, FT-IR spectroscopic analysis, and surface morphology using SEM. In the variation of methylene chloride, methylcellulose has the highest degree of replacement (14 g of 01,17). The formation of methyl cellulose is supported by FT-IR spectroscopy, namely with the appearance of vibration peaks in the wave number area of 3295.0 cm-1, which shows the -OH group, the C-H stretching group at wave number 2892.4 cm-1, the absorption peak that indicates the presence of C-O-C is found in wave numbers 1152.6 cm-1 and 1021.3 cm-1 where it is an asymmetrical and symmetrical stretching vibration. Morphological analysis using SEM showed that cellulose fibers' surface is smoother than methylcellulose. The average size of cellulose and methyl cellulose fibers is 4.791 Î¼m and 3.828 Î¼m, respectively. Morphological analysis using SEM showed that the surface fibers in cellulose were smoother than methylcellulose. The average size of cellulose and methyl cellulose fibers was 4.791 Î¼m and 3.828 Î¼m.